Results from an international phase 2 study of the anti‐CD22 immunotoxin moxetumomab pasudotox in relapsed or refractory childhood B‐lineage acute lymphoblastic leukemia. Issue 5 (15th January 2020) - Shah, Nirali N.; Bhojwani, Deepa; August, Keith; Baruchel, André; Bertrand, Yves; Boklan, Jessica; Dalla‐Pozza, Luciano; Dennis, Robyn; Hijiya, Nobuko; Locatelli, Franco; Martin, Paul L.; Mechinaud, Françoise; et al.
Abstract: Background: In a multicenter phase 1 study of children with relapsed/refractory acute lymphoblastic leukemia (ALL), moxetumomab pasudotox, an anti‐CD22 immunotoxin, demonstrated a manageable safety profile and preliminary evidence of clinical activity. A phase 2 study further evaluated efficacy. Procedure: This international, multicenter, phase 2 study enrolled children with relapsed/refractory B‐cell precursor ALL who received moxetumomab pasudotox 40 µg/kg intravenously every other day, for six doses per 21‐day cycle. The primary objective was to evaluate the complete response (CR) rate. Secondary objectives included safety, pharmacokinetics, and immunogenicity evaluations. Results: Thirty‐two patients (median age, 10 years) were enrolled at 16 sites; 30 received study drug and were evaluable for safety; 28 were evaluable for response. The objective response rate was 28.6%, with three patients (10.7%) achieving morphologic CR, and five patients (17.9%) achieving partial response. Disease progression occurred in 11 patients (39.3%). Ten patients (33.3%) experienced at least one treatment‐related serious adverse event, including capillary leak syndrome (CLS; n  = 6), hemolytic uremic syndrome (HUS; n  = 4), and treatment‐related death ( n  = 1) from pulmonary edema. No differences were observed in inflammatory markers in patients who did or did not develop CLS or HUS. Conclusions: Despite a signal for clinical activity, this phase 2 study was terminated at interim analysis for a CR rate that did not reach the stage 1 target. Preclinical data suggest enhanced efficacy of moxetumomab pasudotox via continuous infusion or in combination regimens; thus, further studies designed to optimize the efficacy and safety of moxetumomab pasudotox in pediatric ALL may be warranted.